KAJIAN YURIDIS TERHADAP CALON PERSEORANGAN DALAM SISTEM PEMILIHAN KEPALA DAERAH SECARA LANGSUNG - Sri Pujiningsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
The individual candidate will become the new competitor for the political party in the depths of the local head election after the Constitution Court enact the judicial review  against  the  Act  32  year  2004  about  the  Government  of  the  Area.  The Constitution court considered that the Act 32  year 2004 that only give space and the  opportunity  to  the  political  party  and  the  combination  of  the  political  party evidently  is  considered  contradictory  to  the  1945  Constitution.  The  Act  32  year 2004  consider  to  close  the  constitutional  right  the  individual  candidate  without going through the political party in the local head election. The Constitution court then say so that the individual candidate without going through the political party or the  combination of the  political party is  enabled to  go along in the  local  head election.  The keyword : The individual candidate, Constitution Court